Time Loop Plot Structure Pattern in the Films Edge of Tomorrow (2014), Happy Death Day (2017) and Palm Springs (2020) - Nugroho, Agustinus Dwi; Ridwan, M. Alif Wijaya (Seni Media Rekam ISI Surakarta, 2024)
Exploration of plot development patterns in narrative structure can be seen from the Time Loop Plot which is used in several films in a very unique way. This plot pattern emphasizes a character trapped in space and time that repeats itself continuously. This qualitative research uses an observational approach that focuses on observing Time Loop Plot patterns and connecting them with three different genre variants, namely Edge of Tomorrow (action-science fiction), Happy Death Day (thriller-horror), and Palm Spring (roman-comedy). This research aims to obtain an overview of the narrative structure pattern